Estimation of 14CO2 amount in the atmosphere - Světlík, Ivo; Molnár, Mihály; Váňa, Milan; Michálek, Václav; Stefanov, Petar (Journal of radioanalytical and nuclear chemistry, 2009)
Carbon from fossil CO 2 emissions, without a significant presence of 14 C, causes dilution of 14 C in the carbon isotopic mixture (Suess effect). Reported 14 C activities are usually connected to radiocarbon amount in the carbon isotopic mixture. Our paper is aimed on estimation of 14 C/ 14 CO 2 amount in the atmosphere (and its trend), utilizing calculation of a 14 C activity concentration. A parameter connected only with a 14 C quantity in the volume or mass unit of air is not influenced by a fossil carbon amount. Such a “robust” parameter can be influenced only by processes connected with 14 C emissions/depositions.